A Simple Oligonucleotide Biochip Capable of Rapidly Detecting Known Mitochondrial DNA Mutations in Chinese Patients with Leber'S Hereditary Optic Neuropathy (LHON). Issue 4 (8th May 2013) - Du, Wei-Dong; Chen, Gang; Cao, Hui-Min; Jin, Qing-Hui; Liao, Rong-Feng; He, Xiang-Cheng; Chen, Da-Ben; Huang, Shu-Ren; Zhao, Hui; Lv, Yong-Mei; Tang, Hua-Yang; Tang, Xian-Fa; et al.
Abstract : Leber's hereditary optic neuropathy (LHON) is a maternally transmitted disease. Clinically, no efficient assay protocols have been available. In this study, we aimed to develop an oligonucleotide biochip specialized for detection of known base substitution mutations in mitochondrial DNA causing LHON and to investigate frequencies of LHON relevant variants in Anhui region of China. Thirty-two pairs of oligonucleotide probes matched with the mutations potentially linked to LHON were covalently immobilized. Cy5-lablled targets were amplified from blood DNA samples by a multiplex PCR method. Two kinds of primary mutations 11778 G > A and 14484 T > C from six confirmed LHON patients were interrogated to validate this biochip format. Further, fourteen Chinese LHON pedigrees and twenty-five unrelated healthy individuals were investigated by the LHON biochip, direct sequencing and pyrosequencing, respectively. The biochip was found to be able efficiently to discriminate homoplasmic and heteroplasmic mtDNA mutations in LHON. Biochip analysis revealed that twelve of eighteen LHON symptomatic cases from the 14 Chinese pedigree harbored the mutations either 11778G > A, 14484T > C or 3460G > A, respectively, accounting for 66.7%. The mutation 11778G > A in these patients was homoplasmic and prevalent (55.5%, 10 of 18 cases). The mutations 3460G > A and 3394T > C were found to co-exist in one LHON case. The mutation 13708G > A appeared in one LHON pedigree. Smaller amount of sampling and reaction volume, easier target preparation, fast and high-throughput were the main advantages of the biochip over direct DNA sequencing and pyrosequencing. Our findings suggested that primary mutations of 11778G > A, 14484T > C or 3460G > A are main variants of mtDNA gene leading to LHON in China. The biochip would easily be implemented in clinical diagnosis.